THE CONTENT OF THE PIRLS STUDY AND ITS IMPORTANCE IN PRIMARY EDUCATION - Kazakova Gulrukh Nuriddin kizi (Modern American Journals, 2026)
This article presents a comprehensive theoretical and analytical study of the PIRLS (Progress in International Reading Literacy Study) international assessment program and its role in the development of primary education. The paper examines the conceptual foundations, objectives, structure, assessment framework, and methodological features of PIRLS, with particular emphasis on its relevance to evaluating reading literacy among primary school students. The study also analyzes the significance of PIRLS results in improving the quality of education, developing reading comprehension skills, enhancing teaching methodologies, and aligning national education systems with international standards. The findings demonstrate that the integration of PIRLS principles into primary education contributes to the formation of functional literacy, critical thinking, and lifelong learning competencies in students.
Keywords: PIRLS, reading literacy, primary education, international assessment, educational quality, reading comprehension.